2019
DOI: 10.2147/ijn.s198116
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vitro comparison of liposomal drug delivery systems targeting the oxytocin receptor: a potential novel treatment for obstetric complications</p>

Abstract: Introduction: Targeted intervention to the uterus has great potential for the treatment of obstetric complications (eg, preterm birth, dysfunctional labor, and postpartum hemorrhage) by improving the effectiveness and safety of therapeutic compounds. In particular, targeting the oxytocin receptor (OTR) is a novel approach for drug delivery to the uterus. The aim of this study was to report the complete data set for the pharmaceutical synthesis and in vitro characterization of PEGylated liposomes conjugated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…These analogs were able to induce behavioral changes out to 24 h indicating longer halflives, though the ability to induce intracellular calcium uncaging through the OXTR was much less than the endogenous peptide (Cherepanov et al, 2017). With respect to receptor antagonism, OXTR antibodies bound to the surface of liposomes have been tested, but only in targeting myometrium at this point (Hua, 2019;Hua and Vaughan, 2019). In summary, the complex nature of OXTR biology, with diverse, context-dependent cellular processing, homology with the vasopressin receptors, and ubiquitous expression peripherally and centrally, present challenges to the implementation of promising treatments.…”
Section: Cellular Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…These analogs were able to induce behavioral changes out to 24 h indicating longer halflives, though the ability to induce intracellular calcium uncaging through the OXTR was much less than the endogenous peptide (Cherepanov et al, 2017). With respect to receptor antagonism, OXTR antibodies bound to the surface of liposomes have been tested, but only in targeting myometrium at this point (Hua, 2019;Hua and Vaughan, 2019). In summary, the complex nature of OXTR biology, with diverse, context-dependent cellular processing, homology with the vasopressin receptors, and ubiquitous expression peripherally and centrally, present challenges to the implementation of promising treatments.…”
Section: Cellular Differentiationmentioning
confidence: 99%
“…These analogs were able to induce behavioral changes out to 24 h indicating longer half-lives, though the ability to induce intracellular calcium uncaging through the OXTR was much less than the endogenous peptide ( Cherepanov et al, 2017 ). With respect to receptor antagonism, OXTR antibodies bound to the surface of liposomes have been tested, but only in targeting myometrium at this point ( Hua, 2019 ; Hua and Vaughan, 2019 ).…”
Section: The Oxtr As a Therapeutic Target For Ischemic Injurymentioning
confidence: 99%
“…82 Nanocarriers such as liposomes, micelles, polymeric nanocarriers, dendrimers, hydrogels, metallic nanocarriers, QDs, carbon-based nanocarriers, exosomes, and viruses have been extensively studied for the design of drug delivery systems. 80,[83][84][85][86][87][88][89][90][91][92][93] The design of nanocarriers for drug delivery offers several advantages, including the improvement of hydrophobic drug stability, thereby making them plausible for administration, the enhancement of biodistribution, and pharmacokinetics. This results in improved efficacy, improvement of the EPR effect, increased selective targeting, reduced adverse effects as a consequence of favored accumulation at target sites, and decreased toxicity by using biocompatible nanomaterials.…”
Section: Gene Therapymentioning
confidence: 99%
“…NP are also able to cross the placenta and treat the fetus, as in hypoxia situations [ 50 ], and through the transport of macromolecules such as immunoglobulin G to fetal circulation [ 51 ]. In the studies ( in vitro ) of Hua and Vaughan [ 52 ] and Hua [ 53 ] was demonstrated the potential of NP (liposomes) for drug targeting to myometrial tissue. Moreover, Li et al [ 54 ] ( ex vivo ), tested NP by targeting of placental tissue for preeclampsia-treatment.…”
Section: Nanotherapymentioning
confidence: 99%